Pengaruh Influencer dan Cita Rasa Terhadap Keputusan Pembelian Pada Pelanggan Restoran Gildak Kertabumi Karawang - Dhio Fajar Ramadhan; Ajat Sudrajat (Peneliti.net, 2022)
This study aims to determine the influencers and flavors that partially and simultaneously influence the purchase decision of Gildak and also to determine the relationship between the Influencer variables of Taste. The data collection method used in this research is descriptive. test, validity test, reliability test, normality test, correlation analysis, T test and F test. There is a positive and partially significant influence between Influencers on Purchase Decisions with a contribution of 0.359 or 35.9%, sig. 0.000 < 0.10 and t count 13.090 > t table 1.966 then Ho is rejected. There is a positive and partially significant effect between Taste and Purchase Decision with a contribution of 0.376 or 37.6%. sig value. 0.000 < 0.10 and t count 13,631 > t table 1,966 then Ho is rejected. The influencer correlation between tastes was 0.675. There is a simultaneous positive and significant influence between influencer and taste on purchasing decisions at Gildak with a contribution of 0.735 or 73.5% and 26.5% can be explained by other variables not examined in this study